2001
DOI: 10.1152/ajpendo.2001.281.6.e1144
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acetate infusion and hyperoxia on muscle substrate phosphorylation after onset of moderate exercise

Abstract: This study investigated whether increased muscle acetylcarnitine provision (acetate infusion) or hyperoxia (100% O(2)) would increase the rate of oxidative phosphorylation and reduce the reliance on muscle substrate phosphorylation after the onset of moderate exercise. Eight subjects completed three randomized trials, each separated by 1 wk: 1) saline infusion for 1 h before exercise, while breathing room air for 20 min before exercise and during 120 s of cycling at 65% maximal exercise (VO(2 max)) (CON), 2) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 40 publications
(63 reference statements)
5
38
0
Order By: Relevance
“…The dose of acetate used in the present study has been shown previously to near maximally acetylate carnitine and free CoASH pools in human skeletal muscle at rest (7,17,25).…”
Section: Methodsmentioning
confidence: 74%
See 2 more Smart Citations
“…The dose of acetate used in the present study has been shown previously to near maximally acetylate carnitine and free CoASH pools in human skeletal muscle at rest (7,17,25).…”
Section: Methodsmentioning
confidence: 74%
“…Studies that have investigated acetyl group utilization during moderate-to-intense skeletal muscle contraction after sodium acetate pretreatment have reported no reduction in the requirement for oxygen-independent ATP production at any contraction time point (7,17,25), implying that elevating acetyl group availability, independently of PDC activation, cannot overcome the period of metabolic inertia and thereby accelerate the onset of mitochondrial ATP production. These previous findings are rather at odds with those reported in the present study; however, this lack of concordance can be accounted for, and on several levels.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, at workloads above this intensity, pretreatment with DCA is unlikely to be associated with a reduction in ATP resynthesis from SLP and an improvement in contractile function. Similarly, based on the findings of Howlett et al (1999) outlined above and the more recent findings of Evans et al (2001), we would propose that there will also be a lower exercise intensity below which acetyl group delivery via the PDC reaction is not limiting towards TCA cycle demands (i.e. where PDC flux and/or fat-mediated acetyl group delivery is sufficient to match the energy demands of contraction).…”
Section: The Acetyl Group Deficitmentioning
confidence: 93%
“…Presumably this exercise intensity equates to one where no increase or decline in acetylcarnitine concentration would be seen upon the initiation of exercise. In this respect, the study by Evans et al (2001) investigated changes in acetyl group availability during 2 min of moderate-intensity (65 % ◊ O 2,max ) exercise in human volunteers following near maximal acetylation of the muscle carnitine and CoASH pools by sodium acetate infusion. In line with our proposal, no changes in acetyl-CoA or acetylcarnitine concentrations were observed following 30 s of exercise in either saline-(control) or sodium acetate-treated subjects, despite the PDC activation that occurred in both groups.…”
Section: The Acetyl Group Deficitmentioning
confidence: 99%